A Pipeline to Increase Public Health Diversity: Describing the Academic Enrichment Components of the Summer Public Health Scholars Program. (December 2021) - Joyner, Danielle M.; Faris, Eman; Hernández, Diana; Moon Howard, Joyce; Fullilove, Robert E.; Cohn, Elizabeth G.; Odlum, Michelle; Mitchell, Dennis; Hutcherson, Hilda
A public health workforce that reflects the increasing diversity of the U.S. population is critical for health promotion and to eliminate persistent health disparities. Academic institutions must provide appropriate education and training to increase diversity in public health professions to improve efforts to provide culturally competent care and programs in the most vulnerable communities. Reaching into the existing talent pool of diverse candidates at the undergraduate level is a promising avenue for building a pipeline to advanced training and professional careers in the field of public health. The Summer Public Health Scholars Program (SPHSP) at the Columbia University Irving Medical Center (CUIMC) is a 10-week summer internship program with a mission to increase knowledge and interest in public health and biomedical sciences. Funded by the Centers for Disease Control and Prevention's (CDC) Undergraduate Public Health Summer Programs, sponsored by the CDC's Office of Minority Health and Health Equity, SPHSP aims to pipeline underrepresented students into public health graduate programs and careers by providing mentorship, academic enrichment, professional development, and field-based placements. The SPHSP is uniquely positioned to offer scholars a program that exposes them to core public health training components through the joint effort of all four CUIMC schools: public health, dentistry, nursing, and medicine. Here, we describe the program's academic enrichment components, which provide advanced and multifaceted public health training opportunities. We discuss the impacts of the program on student outcomes and lessons learned in developing and refining the program model.